PERBANDINGAN TEKNOLOGI WIMAX DENGAN WI-Fi - Nasir, Muhammad (Universitas Bina Darma, 2013)
Some of the technologies are currently implemented, among others, technologies Worldwide Interoperability for Microwave Access (WiMAX) and Wireless Fidelity (Wi-Fi). The second technology is a wireless networking technology that is being rapidly adopted. When this is not the only computer connected to the internet but everyday appliances such as cellular phones, PDAs, and so well connected to the internet. Conducted research aimed to compare the use of WiMAX technology and Wi-Fi interms of service, coverage, standards, frequency speed of both technologies. This research uses the method of collecting data from the literature that the author got from the book and some sources from the internet. Research methods that used is the method of comparative research to findcomparisons of two technologies are researched. Keywords: WiMAX, Wi-Fi, Network